Angka Kuman Pada Alat Makan di Kantin SDN No.47 Telanaipura Kota Jambi - Supriadi Supriadi; Emilia Chandra (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Common environmental-based diseases are often a problem of diarrhea, ARI, and hepatitis caused by an unhealthy environment, including in the canteen environment of the 47 Telanaipura Jambi Primary School. This study aims to determine the Germ Number in eating utensils and how to wash eating utensils in the cafeteria of SDN 47 Telanaipura, Jambi City. This research method uses descriptive design, namely research carried out to describe a situation without giving treatment to the object that aims to study canteen sanitation and the number of germs on eating utensils in the cafeteria SDN No. 47 Jambi City. Analyzing data uni variat and presented in table form then analyzed descriptively and laboratory tests. The results of the research on Germination Figures in Eating Appliances in the SDN 47 Canteen obtained 40% more than the permissible germination rate of 100 colonies / cm² and Washing of food in SDN 47 Telanaipura Jambi had used the recommended washing technique using flowing water. It is suggested that the canteen sword does not use plastic plates, paying attention to the means of storing cutlery and the school is expected to facilitate the provision of closed storage cabinets.